Identification and Association Polymorphisms of TGF-β and IFN-y Genes with Schizophrenia Risk in Iraqi Patients - Anwar Abed Nasser Dhabaan (Journal of Global Pharma Technology, 2016)
Genetics study for IFN-γ (Interleukin-γ) T/A +874 and TGF-β1(Transforming growth factor-beta) +869*C/T genes polymorphisms for schizophrenia patients with mean age 49.95±1.6 was studied by using ARMS-PCR (Amplification refractory mutation system technique). The results revealed the presence of two alleles A and T with three genotypes (TT, TA and AA) for IFN-γ (+874 T/A) gene, and two alleles C and T with three genotypes (CC, TT and CT) for TGF-β1 (+869*C/T). The result show that high frequency for allele A of IFN-γ +874 T/A as compare with T allele in schizophrenia patients samples (n=38) and associated with etiological fraction (EF) of schizophrenia, dependent on values of odds ratio (OR) and confidence intervals (CI), while T allele associated with preventive fraction (PF) of schizophrenia. The ARMS-PCR analysis results present AA and TT homozygotes genotypes of IFN-γ T/A +874 gene was more than in schizophrenia patients as compared with control and showed that AA and TT genotypes associated with EF in schizophrenia risk, while TA heterozygote genotype present in high frequency in control as compared with schizophrenia patients and associated with (PF). The T allele for TGF-β1 (+869*C/T) gene exist in high frequency for schizophrenia patients and associated with (EF) schizophrenia, while C allele associated with (PF) schizophrenia. The TT homozygote genotype frequency of TGF-β1 (+869*C/T) gene was more than in schizophrenia patients and associated with (EF) of schizophrenia, while CC homozygote and CT heterozygotes genotypes present more than in control as compared with schizophrenia patients and associated with (PF).Keywords: Polymorphism, Schizophrenia, IFN-γ T/A +874 and TGF-β1 (+869*C/T) genes.